1984
DOI: 10.1115/1.3246726
|View full text |Cite
|
Sign up to set email alerts
|

Performance of One- and Two-Row Tube and Plate Fin Heat Exchangers

Abstract: Heat exchangers consisting of finned tubes are commonly employed in air conditioning systems, air heaters, radiators, etc. Local measurements of mass transfer coefficients on fins, obtained by Saboya and Sparrow, are very nonuniform. In the present work, an experimental apparatus was set up to measure overall heat transfer coefficients for two-row tube and plate fin heat exchangers. The obtained results, together with Shepherd’s results for one-row exchangers, are used to transform the local mass transfer coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 0 publications
5
19
0
Order By: Relevance
“…Thus, a more accurate prediction of the heat transfer coefficient can be an important work for the device of the high-performance heat exchangers. It is found in [8,9] that the predicted results of the average heat transfer coefficient agree with existing estimates [2,4,10] under the assumption of the ideal isothermal fin. Thus, that the inverse scheme proposed by Chen and Hsu [8] and Chen and Lai [9] has good reliability.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…Thus, a more accurate prediction of the heat transfer coefficient can be an important work for the device of the high-performance heat exchangers. It is found in [8,9] that the predicted results of the average heat transfer coefficient agree with existing estimates [2,4,10] under the assumption of the ideal isothermal fin. Thus, that the inverse scheme proposed by Chen and Hsu [8] and Chen and Lai [9] has good reliability.…”
Section: Introductionsupporting
confidence: 79%
“…Thus, this study applies FLUENT [13] with the two different flow models and appropriate grid points to obtain the heat transfer and fluid flow characteristics of staggered plate-fin and tube heat exchangers with four circular tubes. In order to verify the availability and accuracy of the obtained estimates, the resulting heat transfer coefficient are compared with those given by Rosman et al [2], Saboya and Saboya [4], Huang et al [6] and Chen and Lai [9]. The resulting fin temperature is also compared with the experimental temperature data at the selected measurement locations.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Webb [6] reported that elliptical tubes have better performance than circular tubes. Determination of local and overall heat transfer coefficients is conducted by Rosman et al [7]. Rocha et al [8] analyzed plate fin heat exchangers with circular and elliptical tubes and determined heat transfer coefficients, experimentally.…”
Section: Introductionmentioning
confidence: 99%